The Mediating Role of Feelings of Inferiority in the Relationship between School Bullying and Academic Achievement in Middle School Students with Social Anxiety in Wasit City, Iraq - Jabr Kazem Alkouradi, Salam; Golparvar, Mohsen; Shallal, Abbas Ali; Yousefi, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to determine the mediating role of feelings of inferiority in the relationship between school bullying and academic achievement among students with social anxiety in Wasit City, Iraq. Methods and Materials: The research employed a correlational method, and the statistical population consisted of middle school students in Wasit City, Iraq, in the spring of 2024. From the aforementioned population, 300 students were selected through convenience sampling and responded to three questionnaires: the Academic Achievement Questionnaire (Wells, 2010), the School Bullying Questionnaire (Álvarez-Marin et al., 2022), and the Feelings of Inferiority Questionnaire (Chakreli-Lijia et al., 2017). The data were analyzed using Pearson’s correlation coefficient and structural equation modeling (SEM) with the help of SPSS version 26 and AMOS version 26. Findings: The results showed that school bullying was significantly correlated with feelings of inferiority and academic achievement, and feelings of inferiority were significantly correlated with academic achievement (p < 0.05). The results of the structural equation modeling indicated that feelings of inferiority were a full mediating variable in the relationship between school bullying and academic achievement. Conclusion: Based on the findings of this study, the role of school bullying and feelings of inferiority in academic achievement should be seriously considered in educational environments to better support students.